Headache in Pregnancy, the Puerperium, and menopause - Sader, Elie; Rayhill, Melissa (Seminars in Neurology, 2018)
Headache is a neurologic disorder that displays gender dichotomy. It is well established that there is a strong link between migraine headache and sex hormones, specifically estrogen, which influences the severity of migraines during the menstrual cycle, pregnancy, and menopause. Furthermore, the epidemiology of headaches during pregnancy and the postpartum period is very distinct from that in males or nonpregnant females, in part due to the hemodynamic and hematologic changes that occur during pregnancy. These changes put women at higher risk for cerebral venous thrombosis, hemorrhagic stroke, and hypertensive disorders of pregnancy like preeclampsia, eclampsia, posterior reversible encephalopathy syndrome, and reversible cerebral vasoconstriction syndrome. Headache in pregnancy and the puerperium can be a cause of heightened anxiety in most women, who are concerned not only about the effect of the headache itself on the pregnancy but also about the effect of the treatment options on the pregnancy and the fetus. In this review, we discuss the latest literature on type and distribution of headaches during pregnancy and the postpartum period, and provide a digestible overview of the safety profile of commonly used abortive and prophylactic medications. We also discuss important considerations when treating migraine during menopause.
Keywords: headache; migraine; estrogen; pregnancy; menopause